The effect of narrow‐band ultraviolet B radiation on sleep, happiness, and appetite: A prospective cohort study. Issue 4 (9th January 2021) - Vashurin, Ilan; Barzilai, Aviv; Baum, Sharon; Ohana, Orly; Pavlotsky, Felix; Greenberger, Shoshana
Abstract: Background: The health benefits of sunlight are well documented, including the effects on happiness and sleep. However, only a few studies have investigated the benefits of artificial narrow‐band ultraviolet B (NB‐UVB) radiation. Objectives: To investigate the effect of NB‐UVB on sleep quality, happiness, and appetite. Methods: Patients from a single phototherapy unit were selected, and their epidemiological characteristics were documented. Subjects were asked to complete questionnaires including the Pittsburg Sleep Quality Index (PSQI), Subjective Happiness Scale (SHS), and the Simplified Nutritional Appetite Questionnaire (SNAQ) 4 weeks before and after the initiation of the NB‐UVB therapy. The sample consisted of 52 patients. Results: Four weeks after the initiation of NB‐UVB sessions, sleep quality was significantly improved (the PSQI decreased from 6.5 to 5.23 (t = −3.52, P < .01). In contrast, subjective happiness did not improve (the SHS decreased from baseline 5.5 to 5.2, P > .05). Similarly, appetite did not change (the SNAQ score increased from baseline 14.75 to 15.05, P > .05) and body mass index was not affected by phototherapy. In general, men were found to have better sleep quality before and after UV light therapy. Conclusion: Our data suggest that NB‐UVB exposure over 4 weeks improves sleep quality; however, it does not influence happiness or appetite.